A review on biomass-derived hard carbon anodes for sodium-ion batteries: From carbon precursors to storage mechanisms - LU, Anqi; QIN, Jiaqian (Journal of Metals, Materials and Minerals, 2026)
The rapid development of sustainable energy technologies has intensified the demand for cost-effective and high-performance energy storage systems. Sodium-ion batteries (SIBs) are regarded as one of the most promising alternatives to lithium-ion batteries (LIBs) owing to their low cost, abundant sodium resources, and similar electrochemical mechanisms to LIBs. Hard carbon (HC) has attracted significant attention as the predominant anode material for SIBs due to its low cost, structural tunability, and availability from diverse precursors. Nevertheless, challenges remain, including the unclear Na+ storage mechanism, limited rate capability, and strong dependence on precursor type. This review systematically summarizes recent advances in HC anodes for SIBs, focusing on their structural features and Na+ storage mechanisms, including intercalation–adsorption, adsorption–intercalation, pore-filling, and combined models. Moreover, the influence of different precursors—agricultural and forestry by-products, marine biomass, and industrial wastes—on the microstructure and electrochemical performance of HC is analyzed. Finally, the advantages, limitations, and potential strategies for the rational design of HC are discussed, highlighting opportunities for the development of next-generation SIBs.